A Modular Cascaded Multilevel Inverter Based Shunt Hybrid Active Power Filter for Selective Harmonic and Reactive Power Compensation Under Distorted/Unbalanced Grid Voltage Conditions - Demirdelen, T.; Kayaalp, R. I.; Tumay, M. (Engineering, Technology & Applied Science Research, 2016)
In recent years, shunt hybrid active power filters are being increasingly considered as a viable alternative to both passive filters and active power filters for compensating harmonics. In literature, their applications are restricted to balanced systems and low voltage applications and therefore not for industrial applications. This paper investigates the performance of a modular cascaded multilevel inverter based Shunt Hybrid Active Power Filter (SHAPF) for reactive power compensation and selective harmonics elimination under distorted/unbalanced grid voltage conditions in medium voltage levels. In the proposed control method, reactive power compensation is achieved successfully with a perceptible amount and the performance results of harmonic compensation are satisfactory. Theoretical analysis and simulation results are obtained from an actual industrial network model in PSCAD. The simulation results are presented for a proposed system in order to demonstrate that the harmonic compensation performance meets the IEEE-519 standard.